In-situ cured solid electrolyte, lithium ion battery and preparation method of lithium ion battery

By using in-situ solid electrolytes in lithium-ion batteries, the specific ratios of polymer monomers, lithium salts and deep eutectic electrolytes are used to solve the problem of insufficient ionic conductivity and safety of solid electrolytes in lithium-ion batteries. , achieving high capacity and excellent cycle stability of lithium-ion batteries.

CN119297388APending Publication Date: 2025-01-10HUNAN MEINI TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411341758.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The solid electrolytes of existing solid-state lithium-ion batteries have shortcomings in ion conductivity and safety, and the interface contact of lithium-ion batteries is unstable, especially in the case of silicon-based anodes with large volume changes during the cycle, it is difficult to ensure electrochemical performance. .

Method used

Using in-situ cured solid electrolyte, cured through specific ratios of polymer monomers, lithium salts and deep eutectic electrolytes, forming a high-safe solid electrolyte, ensuring stable contact with the positive and negative interfaces, and improving ions Conductivity.

Benefits of technology

It realizes the high capacity of lithium-ion batteries and excellent room temperature cycle stability, while improving the thermal stability and safety of the batteries, avoiding the safety risks of traditional liquid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297388A_ABST
    Figure CN119297388A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ cured solid electrolyte, a lithium ion battery and a preparation method thereof, the in-situ cured solid electrolyte is prepared by curing the following raw materials: a polymer monomer, a lithium salt, a deep eutectic electrolyte and an initiator, and the mass ratio of the polymer monomer to the lithium salt to the deep eutectic electrolyte to the initiator is 1000: (5000-10): (9000-10): (1000-0.001); the polymer monomer is selected from one or more of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, vinylene carbonate, ethylene oxide and 1, 3-dioxocyclopentane; the deep eutectic electrolyte comprises a deep eutectic lithium salt and a deep eutectic solvent. The high-safety deep eutectic electrolyte is used, the ionic conductivity and safety of the solid electrolyte are effectively guaranteed, in-situ curing and good interface contact between the positive electrode and the negative electrode are achieved, and the finally obtained lithium ion battery shows high capacity and excellent room-temperature cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an in-situ solidified solid electrolyte, a lithium ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been expanding their application areas and gradually replacing traditional batteries due to their advantages such as low self-discharge rate, high energy density, long cycle life, and no memory. However, with the continuous improvement of the energy density of lithium-ion batteries and the expansion of energy storage scale, the safety of lithium-ion batteries has received more and more attention. Traditional lithium-ion batteries mainly use liquid electrolytes, and lithium-ion batteries using flammable and volatile liquid electrolytes have safety hazards such as internal short circuits, leakage, combustion, and even explosion. Using solid electrolytes to replace traditional liquid electrolytes can effectively solve safety problems fundamentally. Solid-state lithium batteries generally include two categories, the first category is inorganic solid-state lithium-ion batteries, and the second category is solid-state polymer lithium-ion batteries.

[0003] Among them, the solid electrolyte in the solid polymer lithium ion battery is mainly composed of polymer, salt and filler. CN104779415A provides a fully solid polymer electrolyte prepared by cross-linking polymerization of siloxane and polyethylene glycol under hot pressing conditions; CN102738510A provides a composite fully solid electrolyte, which includes polyethylene oxide and / or polyethylene oxide derivative organic inorganic hybrid framework compounds and lithium salts. CN109935893A provides a composite solid electrolyte membrane preparation method and lithium ion battery, by coating the solid electrolyte slurry on both sides of the porous support material, the method effectively improves the flexibility and mechanical strength of the solid electrolyte membrane, but it is difficult to ensure that the solid electrolyte completely infiltrates the pores of the porous support material, and the presence of the pores hinders the conduction of lithium ions. However, when all the above solid electrolytes are matched with the positive and negative electrodes, it is difficult to ensure the stability of the interface between the positive and negative electrodes, especially when dealing with silicon-based negative electrodes with huge volume changes during the cycle, it is more difficult to ensure the interfacial ion transmission during the battery cycle, and the electrochemical performance of solid lithium ion batteries is very limited.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides an in-situ solidified solid electrolyte, a lithium ion battery and a preparation method thereof, so as to solve the problem that the ionic conductivity and safety of the existing solid electrolyte cannot meet the requirements and the interface contact of the lithium ion battery is unstable.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] In a first aspect of the present invention, there is provided an in-situ solidified solid electrolyte, wherein the in-situ solidified solid electrolyte comprises the following raw materials which are solidified:

[0008] A polymer monomer, a lithium salt, a deep eutectic electrolyte and an initiator, wherein the mass ratio of the polymer monomer, the lithium salt, the deep eutectic electrolyte and the initiator is 1000:(5000-10):(9000-10):(1000-0.001);

[0009] The polymer monomer is selected from one or more of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, vinylene carbonate, ethylene oxide, and 1,3-dioxolane;

[0010] The deep eutectic electrolyte includes a deep eutectic lithium salt and a deep eutectic solvent.

[0011] Preferably, the lithium salt is selected from one or more of lithium perchlorate, lithium nitrate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0012] Preferably, the deep eutectic lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium chloride, lithium hexafluorophosphate, lithium polysulfide, lithium perchlorate, lithium bromide, lithium iodide, lithium thiocyanate, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium bis(oxalate)borate.

[0013] Preferably, the deep eutectic solvent is selected from one or more of ester compounds, amide compounds, nitrile compounds and sulfonamide compounds.

[0014] Preferably, the molar ratio of the deep eutectic lithium salt to the deep eutectic solvent is 2:1 to 1:50.

[0015] A second aspect of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the above-mentioned in-situ solidified solid electrolyte.

[0016] Preferably, the active material of the positive electrode is one of lithium iron phosphate, lithium cobalt oxide, ternary lithium manganese oxide, ternary lithium nickel oxide, and lithium manganese iron phosphate; and / or, the active material of the negative electrode is one of lithium metal negative electrode, silicon-based negative electrode, graphite negative electrode, lithium titanate, and conversion negative electrode.

[0017] A third aspect of the present invention provides a method for preparing the above-mentioned lithium ion battery, the method comprising the following steps:

[0018] Mixing polymer monomers, lithium salt, deep eutectic electrolyte and initiator according to a mass ratio to obtain a polymer precursor solution;

[0019] The polymer precursor solution is assembled with the positive electrode and the negative electrode, and after in-situ curing, the lithium ion battery is obtained.

[0020] Preferably, the step of mixing the polymer monomer, lithium salt, deep eutectic electrolyte and initiator according to a mass ratio to obtain a polymer precursor solution specifically comprises:

[0021] dissolving a deep eutectic lithium salt in a deep eutectic solvent to obtain a deep eutectic electrolyte;

[0022] The lithium salt is dissolved in the polymer monomer, and then the deep eutectic electrolyte and the initiator are added in sequence to obtain the polymer precursor solution.

[0023] Preferably, the temperature of the in-situ curing is 25-120° C., the time of the in-situ curing is 0.5-48 h, and the battery is allowed to stand for 1-30 h before the in-situ curing.

[0024] Beneficial effects:

[0025] The present invention discloses an in-situ solidified solid electrolyte, a lithium ion battery and a preparation method thereof, wherein the in-situ solidified solid electrolyte can ensure stable contact with the positive and negative electrode interfaces and conform to the current commercial liquid battery process. In addition, in order to take into account both the high ionic conductivity and safety of the electrolyte, unlike the widely used gel electrolyte, the present invention uses a highly safe deep eutectic electrolyte in the solid electrolyte to replace the traditional electrolyte, effectively ensuring the ionic conductivity and safety of the solid electrolyte, and having both in-situ solidification and good interface contact between the positive and negative electrodes, and the lithium ion battery finally obtained exhibits a higher capacity and excellent room temperature cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison of optical photographs of the solid electrolyte before and after curing in Example 1 of the present invention:

[0027] (a) is an optical photograph before curing, and (b) is an optical photograph after curing;

[0028] Figure 2 It is a comparison chart of the cycle performance of the silicon-based negative electrode and the solid electrolyte half-cell in Example 1 and Comparative Example 1 with in-situ curing and non-in-situ curing;

[0029] Figure 3 This is a full battery cycle performance diagram of a solid electrolyte matched with a silicon-based negative electrode in Example 2 of the present invention;

[0030] Figure 4This is a test diagram of the thermal stability of the solid electrolyte in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The present invention provides an in-situ solidified solid electrolyte, a lithium ion battery and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0032] An embodiment of the present invention provides an in-situ solidified solid electrolyte, wherein the in-situ solidified solid electrolyte comprises the following raw materials which are solidified:

[0033] A polymer monomer, a lithium salt, a deep eutectic electrolyte and an initiator, wherein the mass ratio of the polymer monomer, the lithium salt, the deep eutectic electrolyte and the initiator is 1000:(5000-10):(9000-10):(1000-0.001);

[0034] The polymer monomer is selected from one or more of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, vinylene carbonate, ethylene oxide, and 1,3-dioxolane;

[0035] The deep eutectic electrolyte includes a deep eutectic lithium salt and a deep eutectic solvent.

[0036] The embodiment of the present invention optimizes the raw material formula of the solid electrolyte, specifically through the compounding of polymer monomers, lithium salts, deep eutectic electrolytes and initiators, and injects them into lithium-ion batteries after simple mixing, and obtains lithium-ion batteries after in-situ curing. The embodiment of the present invention chooses to mix the deep eutectic electrolyte (DES) with the polymer monomers. Compared with the traditional electrolyte / polymer monomer body mixing, it has the following advantages: ensuring that the polymer monomer segments and DES are mixed evenly; ensuring good fluidity and high safety of the polymer monomers; high safety of the solid electrolyte after curing; the introduction of DES improves the thermal stability of the solid electrolyte, and can operate at higher temperatures (>60°C).

[0037] Specifically, the initiator can be decomposed by heat to generate free radicals, and the free radicals react with the polymer monomer to form a polymer monomer free radical. This reaction is an exothermic reaction. The polymer monomer free radical further reacts with the polymer monomer, and the chain free radicals with more structural units are formed in this cycle. The free radical activity is high and the reaction is finally terminated. Or the nucleophilic or electrophilic initiator attacks the polymer monomer and forms a complex intermediate with the polymer monomer, and further attacks other polymer monomers to finally form a high molecular polymer. Anionic polymerization, cationic polymerization, etc. can also occur in the present invention. Therefore, the polymer monomers defined in the present invention are mainly small molecule polymer materials with double bonds and a certain degree of unsaturation.

[0038] In addition, the present invention further defines the mass ratio of polymer monomer, lithium salt, deep eutectic electrolyte and initiator as 1000:(5000-10):(9000-10):(1000-0.001). Specifically, when the mass ratio of polymer monomer and lithium salt is 1000:(50-2000), this ratio has a higher lithium ion conductivity and a relatively economical cost; when the mass ratio of polymer monomer and deep eutectic electrolyte is 1000:(5000-100), this ratio can ensure good fluidity of the solution and stability of the negative electrode and solid electrolyte and good curing effect; when the mass ratio of polymer monomer and initiator is 1000:(1-0.001), this ratio can ensure a relatively long curing time to facilitate subsequent operations and a good curing effect.

[0039] In some preferred embodiments, the mass ratio of the polymer monomer, lithium salt, deep eutectic electrolyte and initiator is 1000:(1000-100):(1000-100):(0.5-0.001).

[0040] In some embodiments, the lithium salt is selected from one or more of lithium perchlorate, lithium nitrate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluoro(oxalatoborate), lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0041] In some embodiments, the deep eutectic lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium chloride, lithium hexafluorophosphate, lithium polysulfide, lithium perchlorate, lithium bromide, lithium iodide, lithium thiocyanate, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium bis(oxalate)borate.

[0042] In some embodiments, the deep eutectic solvent is selected from one or more of ester compounds, amide compounds, nitrile compounds, and sulfonamide compounds.

[0043] The present invention also adjusts the types and ratios of the polymer monomers, deep eutectic lithium salts and deep eutectic solvents of the solid electrolyte based on the different complexing abilities of the polymer monomers and deep eutectic solvents for different lithium salts, so that a specific type of lithium salt is preferentially decomposed at the positive and negative electrode interfaces to obtain a SEI film that is more suitable for the positive and negative electrodes of the solid electrolyte, which is beneficial to the subsequent stable cycle of the battery.

[0044] In some embodiments, the molar ratio of the deep eutectic lithium salt to the deep eutectic solvent is 2:1 to 1:50.

[0045] Under the molar ratio of the deep eutectic lithium salt to the deep eutectic solvent defined in the present invention, the deep eutectic solution can exhibit better fluidity.

[0046] In some preferred embodiments, the molar ratio of the deep eutectic lithium salt to the deep eutectic solvent is 2:1-1:20.

[0047] An embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the above-mentioned in-situ solidified solid electrolyte.

[0048] Preferably, the active material of the positive electrode is one of lithium iron phosphate, lithium cobalt oxide, ternary lithium manganese oxide, ternary lithium nickel oxide, and lithium manganese iron phosphate; and / or, the active material of the negative electrode is one of lithium metal negative electrode, silicon-based negative electrode, graphite negative electrode, lithium titanate, and conversion negative electrode.

[0049] In addition, the present invention also generates lithium nitride-rich and lithium fluoride-rich SEI films for lithium negative electrodes or silicon-based negative electrodes, respectively. The present invention can also match different types of positive electrode materials such as high-voltage ternary materials, etc., and can be diversified and precisely controlled to adapt to various battery systems. Specifically, for example, for lithium negative electrodes, systems such as LiTFSI / N-methylacetamide with high solubility in lithium nitrate are used to ensure that lithium nitrate decomposes at low voltage at the lithium negative electrode, which is conducive to the generation of lithium nitride SEI films rich in high ion conductivity. For silicon-based negative electrodes, the LiFSI-acetamide system DES is used. The hydrogen bonding between acetamide and FSI is conducive to the generation of silicon-based negative electrode SEI rich in lithium fluoride at low pressure, which is conducive to buffering the expansion of silicon-based negative electrodes and reducing additional SEI generation.

[0050] An embodiment of the present invention provides a method for preparing the above-mentioned lithium-ion battery, wherein a polymer monomer, a lithium salt, a deep eutectic electrolyte and an initiator are mixed according to a mass ratio to obtain a polymer precursor solution;

[0051] The polymer precursor solution is assembled with the positive electrode and the negative electrode, and after in-situ curing, the lithium ion battery is obtained.

[0052] Different from the existing non-in-situ film forming technology, the present invention proposes to use a heat-cured solid electrolyte, which not only ensures stable contact of the interface but also complies with the current commercial liquid battery process. In the obtained in-situ cured lithium-ion battery, since the polymer precursor solution before curing is in liquid state and has good fluidity, its wettability with the positive and negative electrode interfaces can be guaranteed. After in-situ curing, the interface contact between the solid electrolyte and the positive and negative electrodes is good, ensuring the stability of subsequent cycles.

[0053] In some embodiments, the lithium battery uses a separator.

[0054] The preferred dosage of the above-mentioned polymer precursor solution is 2-20g / Ah. If it is lower than this range, the diaphragm cannot be completely wetted. If it is higher than this range, excess polymer precursor solution will penetrate into the positive and negative electrodes and the gasket, affecting electron conduction. At the same time, the presence of excess polymer precursor solution will also lead to an increase in the thickness of the solid electrolyte after curing, increasing the conduction path of lithium ions in the solid electrolyte.

[0055] In some embodiments, the step of mixing the polymer monomer, lithium salt, deep eutectic electrolyte and initiator according to a mass ratio to obtain a polymer precursor solution specifically includes:

[0056] dissolving a deep eutectic lithium salt in a deep eutectic solvent to obtain a deep eutectic electrolyte;

[0057] The lithium salt is dissolved in the polymer monomer, and then the deep eutectic electrolyte and the initiator are added in sequence to obtain the polymer precursor solution.

[0058] In some embodiments, the temperature of the in-situ curing is 25-120° C., the time of the in-situ curing is 0.5-48 h, and the battery is allowed to stand for 1-30 h before the in-situ curing.

[0059] When the in-situ curing temperature is lower than the range defined in the present invention, the material may not be cured. When the in-situ curing temperature is high, the material may implode, and the mechanical properties and flexibility of the obtained material are poor.

[0060] In some preferred embodiments, the temperature of the in-situ curing is 40-80° C., the time of the in-situ curing is 2-36 hours, and the battery is allowed to stand for 3-12 hours before the in-situ curing.

[0061] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only used to illustrate the present invention but not to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] Deep eutectic (DES) electrolyte configuration: A certain amount of deep eutectic lithium salt LiTFSI and succinonitrile are mixed and stirred at room temperature to obtain a clear and transparent solution, wherein the molar ratio of the deep eutectic lithium salt to succinonitrile is 1:5.

[0064] Preparation of polymer precursor solution: dissolve a certain amount of lithium salt LiDFOB in the polymer acrylic acid monomer, the concentration of the lithium salt LiDFOB is 1M, and when the lithium salt is completely dissolved to obtain a transparent clear liquid, add a certain proportion of the deep eutectic electrolyte prepared above, the volume ratio of DES to the polymer acrylic acid monomer is 1:1, continue stirring to obtain a clear and uniform solution, then add 0.5wt.% of the initiator azobisisobutyronitrile, and after the initiator is dissolved, a polymer precursor solution is obtained.

[0065] Solid-state battery assembly

[0066] Button battery assembly: Assemble in the order of negative electrode shell, gasket, negative electrode, separator, polymer precursor solution, positive electrode, gasket, and positive electrode shell. The amount of the above polymer precursor solution is 15 μL, and then cure at 70°C for 5 hours to obtain an in-situ cured solid-state button battery.

[0067] Soft-pack battery assembly: According to the commercial soft-pack battery, the soft-pack battery is wound and stacked to obtain the soft-pack battery core, and the polymer precursor solution prepared above is used to replace the electrolyte for liquid injection. After vacuum standing, hot pressing and curing are performed at a high temperature of 70°C for 5 hours, and the soft-pack battery is obtained by chemical formation and volume separation.

[0068] Example 2

[0069] Deep eutectic (DES) electrolyte configuration: A certain amount of deep eutectic lithium salt LiTFSI and N-methylacetamide are mixed and stirred at room temperature to obtain a clear and transparent solution, wherein the molar ratio of the deep eutectic lithium salt to N-methylacetamide is 1:4.

[0070] Preparation of polymer precursor solution: dissolve a certain amount of lithium salt LiNO3 in the polymer acrylic acid monomer, the concentration of the lithium salt LiNO3 is 0.1M, and when the lithium salt is completely dissolved to obtain a transparent clear liquid, add a certain proportion of the deep eutectic electrolyte prepared above, the volume ratio of DES to the polymer acrylic acid monomer is 2:1, continue stirring to obtain a clear and uniform solution, then add 0.5wt.% of the initiator azobisisobutyronitrile, and after the initiator is dissolved, a polymer precursor solution is obtained.

[0071] Solid-state battery assembly

[0072] Button battery assembly: Assemble in the order of negative electrode shell, gasket, negative electrode, separator, polymer precursor solution, positive electrode, gasket, and positive electrode shell. The amount of the above polymer precursor solution is 20 μL, and then cure at a high temperature of 60°C for 10 hours to obtain an in-situ cured solid-state button battery.

[0073] Soft-pack battery assembly: The commercial soft-pack battery is wound and stacked to obtain a soft-pack battery core, and the polymer precursor solution prepared above is used to replace the electrolyte for liquid injection. After vacuum standing, it is hot-pressed and cured at 80°C, and the capacity is divided to obtain a soft-pack battery.

[0074] Comparative Example 1

[0075] Deep eutectic (DES) electrolyte configuration: A certain amount of deep eutectic lithium salt LiTFSI and succinonitrile are mixed and stirred at room temperature to obtain a clear and transparent solution, wherein the molar ratio of the deep eutectic lithium salt to succinonitrile is 1:2.

[0076] Preparation of polymer precursor solution: dissolve a certain amount of lithium salt LiDFOB in the polymer acrylic acid monomer, the concentration of the lithium salt LiDFOB is 0.2M, and when the lithium salt is completely dissolved to obtain a transparent clear liquid, add a certain proportion of the deep eutectic electrolyte prepared above, the volume ratio of DES to the polymer acrylic acid monomer is 2:1, continue stirring to obtain a clear and uniform solution, then add 0.5wt.% of the initiator azobisisobutyronitrile, and after the initiator is dissolved, a polymer precursor solution is obtained.

[0077] Preparation of non-in-situ solidified electrolyte: The polymer precursor solution was scraped onto the diaphragm and cured at 70°C for 5 h to obtain the solidified polymer electrolyte.

[0078] Solid-state battery assembly

[0079] Button cell assembly: button cell assembly is performed using the positive electrode, the above-mentioned cured polymer electrolyte, and the negative electrode to obtain a non-in-situ cured solid-state button cell.

[0080] Soft-pack battery assembly: The commercial soft-pack battery is wound and stacked to obtain a soft-pack battery core, and the above-mentioned non-in-situ cured polymer electrolyte is used to replace the electrolyte and the separator, and the soft-pack battery is obtained by hot pressing at 70°C and dividing the capacity.

[0081] Comparative Example 2

[0082] Deep eutectic (DES) electrolyte configuration: A certain amount of deep eutectic lithium salt LiTFSI and N-methylacetamide are mixed and stirred at room temperature to obtain a clear and transparent solution, wherein the molar ratio of the deep eutectic lithium salt to N-methylacetamide is 1:4.

[0083] Preparation of polymer precursor solution: dissolve a certain amount of lithium salt LiNO3 in the polymer acrylic acid monomer, the concentration of the lithium salt LiNO3 is 0.1M, and when the lithium salt is completely dissolved to obtain a transparent clear liquid, add a certain proportion of the deep eutectic electrolyte prepared above, the volume ratio of DES to the polymer acrylic acid monomer is 2:1, continue stirring to obtain a clear and uniform solution, then add 0.5wt.% of the initiator azobisisobutyronitrile, and after the initiator is dissolved, a polymer precursor solution is obtained.

[0084] Preparation of non-in-situ solidified electrolyte: The polymer precursor solution was scraped onto the diaphragm and cured at 60°C for 10 h to obtain the solidified polymer electrolyte.

[0085] Solid-state battery assembly

[0086] Button cell assembly: button cell assembly is performed using the positive electrode, the above-mentioned cured polymer electrolyte, and the negative electrode to obtain a non-in-situ cured solid-state button cell.

[0087] Soft-pack battery assembly: The commercial soft-pack battery is wound and stacked to obtain a soft-pack battery core, and the above-mentioned non-in-situ cured polymer electrolyte is used to replace the electrolyte and the separator, and the soft-pack battery is obtained by hot pressing at 80°C and volume separation.

[0088] Performance testing experiment

[0089] 1. Take the optical photographs of the solid electrolyte in Example 1 before and after curing. Figure 1 It can be seen that the polymer precursor solution before curing is a liquid with good fluidity, while after curing, a non-flowable solid electrolyte is obtained.

[0090] 2. Figure 2 The cycle performance comparison diagram of the silicon-based negative electrode and the solid electrolyte half-cell in in-situ curing and non-in-situ curing in Example 1 and Comparative Example 1 is shown in FIG. Figure 2 It can be seen that the in-situ cured battery with silicon-based negative electrode has a capacity retention rate of 80% after 150 cycles at a current density of 0.5 A / g.

[0091] 3. Figure 3 To match the full battery cycle performance of the silicon-based negative electrode using the solid electrolyte in Example 2, Figure 3 It can be seen that after 100 cycles at room temperature, the battery shows almost no capacity decay.

[0092] 4. Figure 4 This is a graph showing the thermal stability of the solid electrolyte in Example 1. Figure 4Optical photographs of commercial diaphragms (left) and the solid electrolyte after solidification in Example 1 (right) at different temperatures. As shown in the figure, at 30°C, both the commercial diaphragm and the solid electrolyte showed good flatness. When the temperature was raised to 100°C, the commercial diaphragm curled, while the solid electrolyte did not change significantly. When the temperature was raised to 150°C, the commercial diaphragm had already shown strong curling deformation, while the solid electrolyte was still flat. When the temperature was raised to 200°C, the commercial diaphragm shrank and curled violently, while the solid electrolyte was still flat. Comparing the above results, the solid electrolyte showed excellent high-temperature stability.

[0093] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. An in-situ solidified solid electrolyte, characterized in that: The in-situ solidified solid electrolyte comprises the following raw materials which are solidified: A polymer monomer, a lithium salt, a deep eutectic electrolyte and an initiator, wherein the mass ratio of the polymer monomer, the lithium salt, the deep eutectic electrolyte and the initiator is 1000:(5000-10):(9000-10):(1000-0.001); The polymer monomer is selected from one or more of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, vinylene carbonate, ethylene oxide, and 1,3-dioxolane; The deep eutectic electrolyte includes a deep eutectic lithium salt and a deep eutectic solvent.

2. The in-situ solidified solid electrolyte according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium perchlorate, lithium nitrate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluoro(oxalatoborate), lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.

3. The in-situ solidified solid electrolyte according to claim 1, characterized in that: The deep eutectic lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium chloride, lithium hexafluorophosphate, lithium polysulfide, lithium perchlorate, lithium bromide, lithium iodide, lithium thiocyanate, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium bis(oxalate)borate.

4. The in-situ solidified solid electrolyte according to claim 1, characterized in that: The deep eutectic solvent is selected from one or more of ester compounds, amide compounds, nitrile compounds, and sulfonamide compounds.

5. The in-situ solidified solid electrolyte according to claim 1, characterized in that: The molar ratio of the deep eutectic lithium salt to the deep eutectic solvent is 2:1-1:

50.

6. A lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is an in-situ solidified solid electrolyte according to any one of claims 1 to 5.

7. The lithium-ion battery according to claim 6, characterized in that: The active material of the positive electrode is one of lithium iron phosphate, lithium cobalt oxide, ternary lithium manganese oxide, ternary lithium nickel oxide, and lithium manganese iron phosphate; and / or, the active material of the negative electrode is one of lithium metal negative electrode, silicon-based negative electrode, graphite negative electrode, lithium titanate, and conversion negative electrode.

8. A method for preparing a lithium ion battery according to claim 6 or 7, characterized in that: The preparation method comprises the following steps: Mixing polymer monomers, lithium salt, deep eutectic electrolyte and initiator according to a mass ratio to obtain a polymer precursor solution; The polymer precursor solution is assembled with the positive electrode and the negative electrode, and after in-situ curing, the lithium ion battery is obtained.

9. The method for preparing a lithium ion battery according to claim 8, characterized in that: The step of mixing a polymer monomer, a lithium salt, a deep eutectic electrolyte and an initiator according to a mass ratio to obtain a polymer precursor solution specifically comprises: dissolving a deep eutectic lithium salt in a deep eutectic solvent to obtain a deep eutectic electrolyte; The lithium salt is dissolved in the polymer monomer, and then the deep eutectic electrolyte and the initiator are added in sequence to obtain the polymer precursor solution.

10. The method for preparing a lithium ion battery according to claim 8, characterized in that: The temperature of the in-situ curing is 25-120° C., the time of the in-situ curing is 0.5-48 hours, and the battery is allowed to stand for 1-30 hours before the in-situ curing.

Citation Information

Patent Citations

  • Solid electrolyte for lithium ion battery and application thereof

    CN102738510A

  • Solid electrolyte of lithium battery and all-solid-state lithium battery

    CN104779415A

  • Solid electrolyte membrane

    CN109935893A